2021
DOI: 10.3389/fcell.2021.583555
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Regulates Transcription Factor-Specific Neurodevelopmental but Not Sexually Dimorphic Gene Expression Dynamics in Zebra Finch Telencephalon

Abstract: Song learning in zebra finches (Taeniopygia guttata) is a prototypical example of a complex learned behavior, yet knowledge of the underlying molecular processes is limited. Therefore, we characterized transcriptomic (RNA-sequencing) and epigenomic (RRBS, reduced representation bisulfite sequencing; immunofluorescence) dynamics in matched zebra finch telencephalon samples of both sexes from 1 day post hatching (1 dph) to adulthood, spanning the critical period for song learning (20 and 65 dph). We identified e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
(94 reference statements)
2
5
1
Order By: Relevance
“…The lack of a MHM region further indicates that in the European crow, the DNA methylation landscape on the Z chromosome does not contribute to regional sex-specific gene expression to achieve dosage compensation. This is consistent with mechanisms detected in zebra finch, where methylation is autonomous from dosage compensating mechanisms in brain tissue (Diddens et al, 2021). Instead, we hypothesize that the female's Z has evolved a chromatin environment that increases permissiveness along the entire chromosome and that gene-specific control of expression is fine-tuned by specific chromatin accessible regions.…”
Section: Epigenetic Patterns Along the Zsupporting
confidence: 87%
“…The lack of a MHM region further indicates that in the European crow, the DNA methylation landscape on the Z chromosome does not contribute to regional sex-specific gene expression to achieve dosage compensation. This is consistent with mechanisms detected in zebra finch, where methylation is autonomous from dosage compensating mechanisms in brain tissue (Diddens et al, 2021). Instead, we hypothesize that the female's Z has evolved a chromatin environment that increases permissiveness along the entire chromosome and that gene-specific control of expression is fine-tuned by specific chromatin accessible regions.…”
Section: Epigenetic Patterns Along the Zsupporting
confidence: 87%
“…Previous high-throughput studies comparing male and female gene expression in developing brains generally found fewer sex differences than our study; however, they assayed larger and more heterogeneous brain areas ( Diddens et al, 2021 ; Tomaszycki et al, 2009 ; Wada et al, 2006 ). While some of these studies used follow-up histochemical methods to assay expression in specific brain nuclei, our approach of quantifying gene expression directly from microdissected tissue is more efficient and sensitive in detecting differential genes.…”
Section: Discussioncontrasting
confidence: 65%
“…For example, studying the similarities and differences in the neural control of complex behaviors shared between mammals and vertebrates, such as learned vocalizations in songbirds and humans, would give insight into understanding the origin of cellular and molecular diversity of similar behaviors between species. Another current limitation of single-cell transcriptome studies of non-primate, non-mouse studies using brain tissue is that thus far the studies have sampled mostly adult brains (Tosches, 2021;Tosches et al, 2018) LG+ cells from ferrets (Johnson et al, 2015) reasons account for this, such as challenges related to procuring tissues from developing organisms or cost, but work is emerging (albeit not at the single-cell level; Diddens et al, 2021). However, performing developmental analyses and fate mapping at single-cell resolution can provide another level of insight into the question of shared evolutionary origin vs convergence.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Another current limitation of single‐cell transcriptome studies of non‐primate, non‐mouse studies using brain tissue is that thus far the studies have sampled mostly adult brains (Tosches, 2021; Tosches et al., 2018). Multiple reasons account for this, such as challenges related to procuring tissues from developing organisms or cost, but work is emerging (albeit not at the single‐cell level; Diddens et al., 2021). However, performing developmental analyses and fate mapping at single‐cell resolution can provide another level of insight into the question of shared evolutionary origin vs convergence.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%